2015
DOI: 10.1007/s00259-015-3141-3
|View full text |Cite
|
Sign up to set email alerts
|

First determination of the heart-to-mediastinum ratio using cardiac dual isotope (123I-MIBG/99mTc-tetrofosmin) CZT imaging in patients with heart failure: the ADRECARD study

Abstract: The ADRECARD study demonstrated that determination of late HMR during cardiac MIBG imaging using dual isotope ((123)I and (99m)Tc) acquisition on a CZT camera (D-SPECT) is feasible in patients with heart failure. A linear correction based on the phantom study yielded a high agreement between (123)I MIBG HMR obtained using a CZT camera and that from conventional planar imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 23 publications
3
58
0
1
Order By: Relevance
“…While data from these are encouraging, given the aforementioned discussion, one must consider the image that derived quantitative parameters from these camera(s) may differ from those reported in the literature upon which clinical use is recommended. [136][137][138] Solid-state cameras may provide the image resolution and detail necessary for higher quality SPECT images that can allow assessment of regional sympathetic activity that might be superior to HMR in predicting adverse cardiac events, particularly arrhythmias. 139 Derivation of the HMR and Washout (Figures 12, 13) As the HMR is currently the key result of a 123 ImIBG study, it is important it be derived in a standard way.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…While data from these are encouraging, given the aforementioned discussion, one must consider the image that derived quantitative parameters from these camera(s) may differ from those reported in the literature upon which clinical use is recommended. [136][137][138] Solid-state cameras may provide the image resolution and detail necessary for higher quality SPECT images that can allow assessment of regional sympathetic activity that might be superior to HMR in predicting adverse cardiac events, particularly arrhythmias. 139 Derivation of the HMR and Washout (Figures 12, 13) As the HMR is currently the key result of a 123 ImIBG study, it is important it be derived in a standard way.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Whether we can still use the previous numerous stock of data and how we can connect the follow-up data in the same series of patients are important issues. Considering the exchangeability of data between the Anger-type camera and D-SPECT, the authors of this study successfully used an anterior view equivalent planogram and introduced a correction formula to standardize the data between the two systems [1].…”
mentioning
confidence: 99%
“…Therefore, an institutional HMR (HMRi) can be converted to the standard HMR (HMRstd) using the following equation: HMRstd = 0.88/CCi × (HMRi − 1) + 1, where CCi is the CC of the institutional camera/collimator system. The CC ranged from 0.5 to 1.0 depending on the collimator type used [1]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…47 Several studies suggested new imaging-based biomarkers to assess the ventricular functions, such as late heartto-mediastinum ratio (HMR) during cardiac metaiodobenzylguanidine (MIBG) imaging in the ADRECARD study, or (123)I-metaiodobenzylguanidine ((123)I-MIBG) imaging in the ADMIRE-HF study (AdreView Myocardial Imaging for Risk Evaluation in Heart Failure). 48,49 The potential role of CMR-derived T1 mapping in evaluating myocardial fibrosis was demonstrated by several studies, which showed that this new biomarker can independently predict invasively measured LV stiffness. 50 …”
Section: Recent Imaging-based Biomarkersmentioning
confidence: 99%